Seminal cadmium affects human sperm motility through stable binding to the cell membrane - Pappalardo, Claudia; Cosci, Ilaria; Moro, Giulia; Stortini, Angela Maria; Sandon, Annalisa; De Angelis, Cristina; Galdiero, Giacomo; Trifuoggi, Marco; Pivonello, Rosario; Pedrucci, Federica; Di Nisio, Andrea; Foresta, Carlo; et al. (Frontiers in Cell and Developmental Biology, 2023)
Environmental pollutants are claimed as major factors involved in the progressive decline of the fertility rate worldwide. Exposure to the heavy metal Cadmium (Cd) has been associated with reproductive toxicity due to its ionic mimicry. However, the possible direct accumulation of Cd in human sperm cells has been poorly investigated. In this study we aimed to clarify the possible direct effect of Cd exposure on sperm function, through the analysis of its cell accumulation. Semen sample from 30 male subjects residing in high environmental impact areas, and adhering to the “Exposoma e Plurifocalità nella Prevenzione Oncologica” campaign for testis cancer prevention, were compared with semen sample from 15 males residing in low exposure areas. Semen levels and cell Cd content were quantified by inductively-coupled plasma (ICP) spectroscopy. Cell Cd distribution was assessed by scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDS). The impact of Cd on sperm function was evaluated by the in vitro exposure to the heavy metal, whilst possible scavenging approaches/agents were assessed. In addition to higher values of semen Cd, exposed subjects showed a reduction of total motile sperm fraction compared to not-exposed controls (59.6±13.6% vs 66.3±7.3%, P=0.037). Semen Cd levels were also significantly correlated with SEM-EDS signals of Cd detected on sperm head and neck (respectively =0.738, P<0.001 and =0.465, P<0.001). In vitro-2 hours exposure to 0.5 M Cd was associated with a significant reduction of sperm progressive motility. Scavenging approaches with either hypo-osmotic swelling or 10 M reduced glutathione were ineffective in blunting cell Cd and restoring motility. The reduction of exposure levels appears as the main approach to reduce the reproductive issues associated with Cd.